2011
DOI: 10.1007/s11577-010-0124-z
|View full text |Cite
|
Sign up to set email alerts
|

Wie verändert sich die Religiosität im Lebensverlauf?

Abstract: Zusammenfassung: der beitrag untersucht mit daten des Sozio-oekonomischen Panels und Fixed-Effects-Regressionsmodellen die Veränderung der Kirchgangshäufigkeit im Lebensverlauf. Im Zeitraum 1992-2007 ist altersübergreifend ein leichter Rückgang zu beobachten. Dieser im Sinne einer Säkularisierung interpretierbare Periodeneffekt wird durch einen positiven Alterseffekt konterkariert. Der positive Einfluss des Lebensalters schwächt sich jedoch mit fortlaufender Kalenderzeit tendenziell ab. Dies kann ebenfalls als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It was found that religiosity tends to decrease during young adulthood (Hayward & Krause, 2013), but then increases slightly during middle and late adulthood (Bleidorn et al, 2022). Life events such as entering the first marriage, having school-aged children and entering widowhood tend to increase the frequency of attending religious services (Lois, 2011).…”
Section: The Impact Of Religiosity On Trajectories Of Lifetime Fertil...mentioning
confidence: 99%
“…It was found that religiosity tends to decrease during young adulthood (Hayward & Krause, 2013), but then increases slightly during middle and late adulthood (Bleidorn et al, 2022). Life events such as entering the first marriage, having school-aged children and entering widowhood tend to increase the frequency of attending religious services (Lois, 2011).…”
Section: The Impact Of Religiosity On Trajectories Of Lifetime Fertil...mentioning
confidence: 99%
“…It was found that religiosity tends to decrease during young adulthood (Hayward & Krause, 2013), but then increases slightly during middle and late adulthood (Bleidorn, Lenhausen, Schwaba, Gebauer, & Hopwood, 2022). Life events such as entering the first marriage, having school-aged children and entering widowhood tend to increase the frequency of attending religious services (Lois, 2011).…”
Section: The Impact Of Religiosity On Trajectories Of Lifetime Fertil...mentioning
confidence: 99%